2015
DOI: 10.1111/pce.12605
|View full text |Cite
|
Sign up to set email alerts
|

ASG2 is a farnesylated DWD protein that acts as ABA negative regulator in Arabidopsis

Abstract: The tagging-via-substrate approach designed for the capture of mammal prenylated proteins was adapted to Arabidopsis cell culture. In this way, proteins are in vivo tagged with an azide-modified farnesyl moiety and captured thanks to biotin alkyne Click-iT® chemistry with further streptavidin-affinity chromatography. Mass spectrometry analyses identified four small GTPases and ASG2 (ALTERED SEED GERMINATION 2), a protein previously associated to the seed germination gene network. ASG2 is a conserved protein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 80 publications
(91 reference statements)
0
39
0
Order By: Relevance
“…The Arabidopsis ABA-hypersensitive mutant era1 ( enhanced response to ABA1 ), harboring a disruption or deletion of the gene for the β-subunit of protein farnesyltransferase [2932], exhibits enhanced ABA-induced stomatal closure due to the activation of a guard cell S-type anion channel and increased cytosolic Ca 2+ levels in guard cells [29]. Although the role of ERA1-mediated protein farnesylation remains unclear, farnesylated CYP85A2 (a cytochrome P450 enzyme implicated in brassinosteroid biosynthesis) and ASG2 (a WD40 protein involved in seed germination) proteins have recently been shown to act as negative regulators of ABA responses in Arabidopsis [33, 34]. Furthermore, repression of ERA1 has been shown to enhance drought resistance in Arabidopsis [31, 35], Brassica napus (canola) [35, 36], Triticum aestivum (wheat) [37], and Oryza sativa (rice) [38].…”
Section: Introductionmentioning
confidence: 99%
“…The Arabidopsis ABA-hypersensitive mutant era1 ( enhanced response to ABA1 ), harboring a disruption or deletion of the gene for the β-subunit of protein farnesyltransferase [2932], exhibits enhanced ABA-induced stomatal closure due to the activation of a guard cell S-type anion channel and increased cytosolic Ca 2+ levels in guard cells [29]. Although the role of ERA1-mediated protein farnesylation remains unclear, farnesylated CYP85A2 (a cytochrome P450 enzyme implicated in brassinosteroid biosynthesis) and ASG2 (a WD40 protein involved in seed germination) proteins have recently been shown to act as negative regulators of ABA responses in Arabidopsis [33, 34]. Furthermore, repression of ERA1 has been shown to enhance drought resistance in Arabidopsis [31, 35], Brassica napus (canola) [35, 36], Triticum aestivum (wheat) [37], and Oryza sativa (rice) [38].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the downregulation of 2 CUL4-DDB1 complexes (DET1 and DWA1/DWA2) results in upregulation of other CUL4-DDB1 complexes that are negative regulators of ABA signaling, such as those containing DWA3, ABD1, or the recently described ALTERED SEED GERMINA-TION 2 (ASG2). 22,23,30 This would result in decreased ABA signaling and increased germination.…”
Section: Discussionmentioning
confidence: 99%
“…Given that there are at least 5 DDB1-CUL4 complexes that negatively regulate ABA signaling (DWA1/2, DWA3, ABD1, DDA1, ASG2), 20,[22][23][24]30 one would expect loss of DDB1A to result in increased ABA signaling and therefore less germination. This is in fact what we observed in salt and mannitol conditions in both the det1 and wildtype backgrounds.…”
Section: 31mentioning
confidence: 99%
“…Among these WDR proteins, 85 and 78 are putative DWD proteins in Arabidopsis and rice, respectively [14] whereas out of 269 putative WDR proteins, 100 are DWDs in tomato [15]. A total of 27 Arabidopsis DWD proteins interact with DDB1 protein [9, 1618]. These studies have provided insights into the biological role of many of the DWD proteins.…”
Section: Introductionmentioning
confidence: 99%
“…WDR55 has been shown to interact with DDB1 and that this interaction was required for gametogenesis and seed development [17]. Most recently, it has been reported that ASG2 can act as negative regulator to respond ABA via its interaction with DDB1 in Arabidopsis [18]. …”
Section: Introductionmentioning
confidence: 99%